Deciphering the gut microbiome’s metabolic code: pathways to bone health and novel therapeutic avenues - Hwang, Daniel; Chong, Esther; Li, Yanxiu; Li, Yanling; Roh, Kangsan (Frontiers in Endocrinology, 2025)
The gut microbiome plays an important role in the protection against various systemic diseases. Its metabolic products profoundly influence a wide range of pathophysiological events, including the regulation of bone health. This review discusses the recently established connections between the gut microbiome and bone metabolism, focusing on the impact of microbiome-derived metabolites such as SCFAs, Bile Acids, and tryptophan to the control of bone remodeling and immunoreactions. Recent advances in metagenomics and microbiome profiling have unveiled new exciting therapeutic opportunities, ranging from the use of probiotics, prebiotics, engineered microbes, and to fecal microbiota transplantation. Understanding of the interplay among diet, microbiota, and bone health provides new avenues for tailored interventions aimed at reducing disease risk in osteoporosis and other related disorders. By drawing knowledge from microbiology, metabolism, and bone biology, this review highlights the potential of microbiome-targeted therapies to transform skeletal health and the management of bone diseases.